OPSEARCH - Mandal, Birendra Nath.; Deshmukh, S. G.; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer.)
The journal OPSEARCH published by the Operational Research Society of India (ORSI) is a national forum set up with the objective of promoting the education and applications of Operational Research (OR) in day-to-day environment in business, industry and other organizations.
Keywords: Management; Operations research; Decision making; Mathematics; Operations Research/Decision Theory; Management; Mathematics, general